Kitab Kuning dan Pembentukan Karakter Religius Muslim Indonesia - Syaifulloh Yusuf; Dzulkifli Hadi Imawan (Islamika Inside: Jurnal Keislaman dan Humaniora, 2020)
Abstract: This article examines kitab kuning (lit. yellow books: i.e, traditional or classical Islamic texts taught in pesantrens) and the formation of the religious character of Muslims in Indonesia. The study of religious character values ​​in the 'kitab kuning' was carried out at the State Madrasah Aliyah of the Religious Program (MANPK) MAN 1 Yogyakarta. MAPK provides additional 'kitab kuning' class to students so that they can become superior students in religious insight, nationality and the formation of Muslim character in Indonesia. Therefore, this study is important to determine the formation of Muslim character in Indonesia through learning the 'kitab kuning'. Using qualitative approach, this field research used interviews, observation and documentation in data collection. The result is that the 'kitab kuning' namely Ta'lim al-Muta'allim influences the formation of religious character values ​​for Indonesian Muslims. These character values ​​include; (1) maintaining knowledge, (2) respecting teachers and friends, (3) glorifying books, diligently studying and worshiping, (4) avoiding arrogance and humiliating others, (5) being patience in learning and discussion, (6) maintaining integrity (upholding the value of honesty), and (7) being responsible.